Jaws - Spielberg, Steven; Universal Picture (Universal Pictures, 2000)
New police chief Brody on the resort island of Amity recommends closing the beaches after discovering the gristly remains of a young woman. Suspecting a shark attack, he appeals to Mayor who motivated by holiday revenue, insists on keeping the shores open for the 4th day of July weekend. After the shark ravages two young victims, chief Brody teams up with a cocky, young ichthyologist, Hooper, and, a sea-worn shark fisher, Quint, to hunt and destroy the monstrous 25- feet great whale.